Authority of the Indonesian Broadcasting Commission (KPI) over YouTube and Netflix according to law number 32 of 2002 concerning broadcasting - Astria Yuli Satyarini Sukendar; Amanda Raissa; Tomy Michael (Institute Of computer Science (IOCS), 2023)
Today there are many developments in broadcasting technology in Indonesia, educational and quality broadcasts are an important requirement for everyone. This is because quality broadcasts will form a quality society as well. Broadcasting technologies that are currently popular and widely discussed and widely accessed by people in Indonesia are Youtube and Netflix, people who want to access videos and films will be spoiled for convenience provided by these platforms. But what is unfortunate about the existence of Youtube and Netflix is that there are so many shows that can be accessed by everyone and also children without prior screening, supervision and control by the Indonesian Censorship Agency. For now.